1967
DOI: 10.1111/j.1365-2621.1967.tb00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lipid Composition of Sweet Potatoes as Affected by Controlled Storage

Abstract: SUMMARY— The fatty acid composition of the lipids extracted from Georgia Red and Centennial varieties of sweet potatoes was studied to determine changes during storage at 15.5, 10, and 4.5°C. The two varieties did not differ initially in the relative proportions of fatty acids. However, changes in fatty acid composition were noted during storage and appeared to be mere pronounced at low storage temperatures. The most consistent changes noted were an increase in tetra‐cosaenoic acid and a decrease in short chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Further comparison of the make-up of Centennial lipids as found by Boggess et al (1967;1970) and this study is not possible because of the differences in methodology.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Further comparison of the make-up of Centennial lipids as found by Boggess et al (1967;1970) and this study is not possible because of the differences in methodology.…”
Section: Resultsmentioning
confidence: 76%
“…THE LIPID content of cured Centennial sweet potatoes from this study was found to be 2.7% (dry weight). Boggess et al (1967;1970) found 1.6% lipids for Centennials. This discrepancy could easily be due to differences in curing and storage or methodology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total lipids of pureed raw, Centenntial sweet potatoes, were found to be 2.45% on a dry weight basis. Walter et al (1971) reported 2.7% and Boggess et al (1967Boggess et al ( , 1970 1.6% total lipids. In the work reported here, neutral lipids were found to be the most abundant at 48.1%, followed by glycolipids, 31.2% and phospholipids, 20.7%.…”
Section: Preparation Of Methyl Esters Of Long Chain Fatty Acidsmentioning
confidence: 95%
“…Little is known about the lipids of sweet potatoes ahd their changes upon storage. Boggess et al (1967) studied the lipid changes of sweet potatoes after curing and storage for 5 months. They separated lipids into three classes: a nonphosphorus fraction, a lecithin fraction, and a cephalin fraction and found changes in both total and fraction lipids.…”
Section: Dehydrationmentioning
confidence: 99%